Obesity, cardiometabolic diseases and aging-the role of Ataxia Telangiectasia Mutated protein kinase: optimization of in vitro lipotoxic H9c2 cardiomyoblasts and rat aortic endothelial cell models for cell signalling analysis - Rabela, Vuyisane Michael (Stellenbosch : Stellenbosch University, 2024)
Thesis (MSc)--Stellenbosch University, 2024.